Putting theory into theory: Thematic value of research in public administration teaching. (March 2016) - Barber, Stephen; Luke, Peter
Research can be a powerful tool informing public administration teaching. This article takes the distinctive approach of exploring its use through the prism of the research itself by considering 10 publications by the article's authors. The existing literature revolves around students learning about the craft of research or research findings. By consolidating these ideas to observe the practicalities of doing research and the value of indirect findings, the article advances the approach to demonstrate how concepts within research can be of reflective worth for learners with what it terms the "thematic value" of research.